Rhombic dodecahedron-like CoMoO4/C composite: A facile construction and excellent electrochemical performances for lithium-ion batteries. Issue 15 (15th October 2020) - Wang, Li; Wang, Xuejia; Zhong, Linping; Liang, Wenfei; Liu, Mengjiao; Zhao, Yan; Lai, Xin; Bi, Jian; Gao, Daojiang
Abstract: The design of an unique micro/nanoscale structure and the composite construction with conductive materials are the two effective means to improve the electrochemical energy storage for transition metal oxides anode. However, the rational design and controllable synthesis of complex ternary transition metal oxide (such as CoMoO4 ) composite with polyhedron morphology is still a challenge. Herein, we report a facile and effective strategy to synthesize rhombic dodecahedron-like (denoted as RD-like) CoMoO4 /C composite, which involves the initial pre-reaction between the newly made ZIF-67 with H2 MoO4 in ethanol and the subsequent calcination for the resultant precursor powders in air. It is found that the calcination temperature plays a key role in determining the microstructures and the content of the generated activated carbon. Below 400 °C, the CoMoO4 /C composite cannot be derived, whereas the perfect and regular RD morphology for CoMoO4 /C composite also cannot be acquired over 500 °C. Moreover, a plausible mechanism for the construction of RD-like CoMoO4 /C composite has also been proposed and explained. Benefiting from its unique structural merits and the significant synergistic effect of the in-situ composite activated carbon, the obtained RD-like CoMoO4 /C composite at 500 °C displays outstanding electrochemical performances with high reversible capacity (532.5 mAh g −1 /500th cycle at 1C), excellent cycling stability and better rate capability when it tested as anode materials for lithium-ion batteries. It is conceivable that this three-in-one strategy can be extended to design and construct other cobalt-based oxyacid/C composites with unique polyhedron morphology, and markedly boost their electrocehmical performaces.